1987
DOI: 10.1111/j.2044-8295.1987.tb02260.x
|View full text |Cite
|
Sign up to set email alerts
|

The stress of the transition to university: A longitudinal study of psychological disturbance, absent‐mindedness and vulnerability to homesickness

Abstract: A longitudinal study was conducted to examine the effects of the transition to university in residential and home-based students. All students showed evidence of raised psychological disturbance and absent-mindedness following the transition. Although there were no differences between resident and home-based students in this respect, those who reported homesickness were distinguished from the remainder in terms of higher levels of psychological disturbance and cognitive failure following the transition to univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
270
2
13

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(296 citation statements)
references
References 18 publications
(23 reference statements)
11
270
2
13
Order By: Relevance
“…The symptomatology mainly includes depression and anxiety, and may come about with a state of apathy, withdrawal and lack of interest; loneliness, nervousness, insecurity and loss of control may also appear, as well as psychosomatic disorders (Archer et al 1998;Stroebe et al 2015;Van Tilburg et al 1996). Among students, homesickness can reduce their ability to concentrate, cause lack of memory and induce social isolation and difficulties in adapting to university life; it has been shown that high levels of homesickness can trigger dropout (Fisher and Hood 1987;Thurber and Walton 2012). In a study with non-resident first-year university students, Urani and colleagues (Urani et al 2003) showed a correlation between social anxiety and homesickness at the beginning of the academic semester: however, these feelings decrease over time.…”
Section: Impact Of Homesickness On Psychological Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…The symptomatology mainly includes depression and anxiety, and may come about with a state of apathy, withdrawal and lack of interest; loneliness, nervousness, insecurity and loss of control may also appear, as well as psychosomatic disorders (Archer et al 1998;Stroebe et al 2015;Van Tilburg et al 1996). Among students, homesickness can reduce their ability to concentrate, cause lack of memory and induce social isolation and difficulties in adapting to university life; it has been shown that high levels of homesickness can trigger dropout (Fisher and Hood 1987;Thurber and Walton 2012). In a study with non-resident first-year university students, Urani and colleagues (Urani et al 2003) showed a correlation between social anxiety and homesickness at the beginning of the academic semester: however, these feelings decrease over time.…”
Section: Impact Of Homesickness On Psychological Well-beingmentioning
confidence: 99%
“…Stroebe et al 2015). The transition to university, for example, is a life-event that could have negative effects on psychological functioning (e.g., Hamaideh 2011;Pellicer et al 2002), and the move away from the family could be an additional stress factor for non-residential students, who may perceive their entrance to university as stimulating, but also stressful (Fisher and Hood 1987). Additional elements that can increase the loneliness of non-residential students include the discrimination perceived by foreign students and their difficulty to integrate in the academic context (Poyrazli and Lopez 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The psychological adjustment of young adults following different pathways might differ. Empirically, the transition to university has been associated in some studies with lower overall wellbeing, higher anxiety, homesickness, depression, and absent-mindedness (Beck, Taylor, & Robbins, 2003;Cooke et al, 2006;Fisher & Hood, 1987). Cooke et al (2006) monitored the psychological well-being of 4,699 students before and across their first year at university.…”
Section: Autonomous Regulation and Subjective Well-beingmentioning
confidence: 99%
“…26 Severe homesickness in children is associated with social problems, behavior problems, significant symptoms of depression and anxiety, coping deficits, and feelings of helplessness. 9,22,[27][28][29] In academic settings, homesickness among adolescents and young adults can be associated with nontraumatic ailments, [30][31][32] academic difficulties, [33][34][35] absentmindedness, 30,31,33,34 low self-esteem, 34,36 and/or obsessive thoughts and behaviors. 30,31 Unfortunately, data do not exist on the incidence and severity of homesickness in children with cognitive or developmental delay.…”
Section: Definitions Epidemiology and Diagnosismentioning
confidence: 99%